Mothers against Radiation: Effort to become a ‘professional’ organization and its failure - Löschke, Ayaka (2021 Annual Conference of the German Association for Social Science Research on Japan “Continuity and Change 10 years after 3.11”, 2021)
Immediately after Fukushima, many mothers became politically active to protect children from radiation, more specifically to abolish the 20 mSv criterion, the annual radiation exposure limit that was raised by the government twentyfold immediately after Fukushima. While most of them failed to keep their engagement around 2015, the Kodomo-tachi wo Hōshanō kara Mamoru Zenkoku Nettowāku (the National Network of Parents to Protect Children from Radiation; the “Kodomozenkoku”) maintained their engagement. Since its establishment in July 2011, more than 340 local groups against radiation from all over Japan joined the Kodomozenkoku as rank-and-file members. The Kodomozenkoku held study groups to warn the public about health risks from low-level radiation exposure in the Tokyo metropolitan area until 2020. Why could the Kodomozenkoku survive for ten years? Why did the Kodomozenkoku fail to keep its advocacy? To examine changes in the Japanese civil society after Fukushima, this article analyzes changes in mothers’ advocacy and organization, using the Kodomozenkoku as a case study, within the framework offered by organizational theory and social movement theory. It focuses on the advocacy, internal structuration, and interorganizational relations that the Kodomozenkoku has undergone for ten years. The Kodomozenkoku was converted from a loose tied volunteer group to a well-organized, centralized Non-Profit Organization (NPO) in 2014. But the Kodomozenkoku shifted its focus from advocacy to non-advocacy activities in spite of a broadened source base and improved decision-making structure. This research is based mainly on the results from 63 qualitative interviews that were conducted between 2013 and 2017. The government policy change regarding radiation in 2013 is not the only reason for the decline of the Kodomozenkoku’s advocacy. This research argues that the Kodomozenkoku’s dependence on other prominent activists, in particular its tendency not to leap into the spotlight as activists in public events, but rather to play a supporting role as a moderator or facilitator also caused a decline in attraction as a political actor.<br
Keywords: Fukushima; advocacy; social movement; organization; NPO